POSITIONING SPICES AS A TOURISM PRODUCT FOR FOREIGNERS: A STUDY FROM THE INDIAN PERSPECTIVE - Datta, Bivek (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2022)
Spice Tourism is an emerging sector in tourism majorly focusing on the impact of spices on tourism choices, growth, and distinctiveness. Because of the fascinating role of spices in tourism growth and diversification in new emerging economies, there is an increased demand for the promotion and growth of spice tourism in many developing economies like India and Sri Lanka. However, a comprehensive investigation is lacking pertaining to spice tourism. In this situation, the present research attempts to bring together and discuss the role of spices as an instrument to entice foreign tourists visiting India. A structured survey instrument in the form of a questionnaire was used for data collection from 400 inbound foreign tourists at the Indira Gandhi International (IGI) Airport, New Delhi. This study has provided directions to the practitioners and academicians in uncovering a diversity of perspectives on the emerging spice tourism market. It also suggests the role of spices as a tactical tool to recreate the destination image of India as a spice tourism destination. The research can also be utilized to examine the foreign tourist’s spice preferences in India, which can be used by stakeholders and practitioners to entice and enhance their revisit to India.